Development of Canva Application Assisted Learning Media in Class XII Advanced Study Materials with 4-D Models - Mulyati, Iis; Indri Astuti; Eny Ernawaty (JTP - Jurnal Teknologi Pendidikan, 2022)
This study aims to share learning media using Canva and to find out student responses. This type of research is research using the 4-D development example developed by S. Thiagarajan using 4 stages, namely: the definition stage (Define), the planning stage (Design), the development stage (Develop), the dissemination stage (Disseminate). The research sample was class XII students totaling 38 students. Research instruments include questionnaires and needs analysis in this study using observation, interviews and questionnaires. The technique used in the analysis of this research data is quantitative descriptive analysis. Learning media using Canva can increase student learning motivation. The use of this media is very effective, both offline and online. The development of Canva learning media is also based on phenomena in the field, namely that there has not been development of learning media using Canva for use at MAN 1 Pontianak, as a result it is necessary to develop learning media using Canva that are valid and practical. The purpose of this study is to share learning media using Canva which is used at MAN 1 Pontianak. It is hoped that this learning media can be used by teachers, especially guidance and counseling teachers for learning in advanced study material classes.